2022
DOI: 10.1093/cvr/cvac104
|View full text |Cite
|
Sign up to set email alerts
|

Impaired regulation of MMP2/16–MLCK3 by miR-146a-5p increased susceptibility to myocardial ischaemic injury in aging mice

Abstract: Aims Aging impairs cardiac function and increases susceptibility to myocardial ischemic injury. Cardiac myosin light chain kinase (MLCK3) phosphorylates cardiac myosin regulatory light chain (MLC2), controlling sarcomere organization and cardiomyocyte contraction. Dysregulation of MLCK3 and phosphorylated MLC2 (p-MLC2) contributes to heart failure after myocardial infarction (MI). We aimed at exploring how the MLCK3-p-MLC2 axis changes in aging hearts post MI and at investigating the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Troxerutin-induced repression of miR-146a-5p moderates cardiomyocyte apoptosis in myocardial I/R injury [ 28 ], whereas miR-146a-5p upregulation by silencing of long noncoding RNA SRY-box transcription factor 2 overlapping transcript also contributes to the remission of this disease [ 29 ]. Intriguingly, miR-146a-5p can mediate a compensatory regulation that protects cardiac function after MI, but this compensatory regulation is supposed to be inhibited by aging, leading to elevated susceptibility to myocardial I/R injury [ 58 ]. Based on our results, the total m6A was increased after H/R treatment, which may be due to METTL14-mediated m6A modification on pri-miR-146a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Troxerutin-induced repression of miR-146a-5p moderates cardiomyocyte apoptosis in myocardial I/R injury [ 28 ], whereas miR-146a-5p upregulation by silencing of long noncoding RNA SRY-box transcription factor 2 overlapping transcript also contributes to the remission of this disease [ 29 ]. Intriguingly, miR-146a-5p can mediate a compensatory regulation that protects cardiac function after MI, but this compensatory regulation is supposed to be inhibited by aging, leading to elevated susceptibility to myocardial I/R injury [ 58 ]. Based on our results, the total m6A was increased after H/R treatment, which may be due to METTL14-mediated m6A modification on pri-miR-146a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that upregulating miR-146a-5p expression in cardiosphere-derived cells inhibits the production of proinflammatory cytokines and transcripts, hence reducing myocardial fibrosis ( 25 ). Additionally, miR-146a-5p carried by exosomes was reported to downregulate matrix metalloprotease 2/16 expression in cardiomyocytes, which could improve cardiac contractile function and decrease susceptibility after myocardial infarction ( 26 ). Furthermore, a decreased miR-146a-5p level was linked to an increased risk of non-stroke severe adverse cardiovascular events in AF ( 27 ).…”
Section: Discussionmentioning
confidence: 99%